Regional variation in Hopewell copper use - Kocik, Cynthia A. (My University, 2012)
The Hopewell complex arose in the Middle Woodland period around 2000 years ago in the Midwest United States. Conical burial mounds, elaborate artifacts, and acquisition of exotic materials characterized Hopewell. Questions remain regarding how to define Hopewell and how and why Hopewellian ideas and material culture spread. However, socio-religious ideas have garnered recent attention. This study compared three Hopewell regions to explore these questions. The use of copper was investigated in the Hopewell center in Ohio, the Havana variant based in the Illinois River Valley, and Hopewell-affiliated sites in southwestern Wisconsin. Analysis of the form and style, context, and metric attributes of copper artifacts addressed how and why this material was used, as well as offering insight into interregional relationships. While similarities between the Havana and Wisconsin regions were found, certain characteristics of the Wisconsin sites suggest interaction with the Hopewell core that did not run through the Havana region.
Keywords: Hopewell culture; Copper